Meningkatkan Motivasi Berprestasi Peserta Musabaqah Tilawatil Qur’an - Setiawan, Muhammad Andri; Permatasari, Nina; Novitawati (Yayasan Sagita Akademia Maju, 2024)
Musabaqah Tilawatil Qur'an (MTQ) is an important religious competition for the Muslim community in Indonesia. However, many participants face challenges in fostering optimal achievement motivation. Observations in Tapin Regency revealed that inadequate psychological support is a major factor affecting participants' motivation. This community service activity aims to enhance the achievement motivation of MTQ participants through psychological training. The training was conducted on April 6, 2024, with 60 participants, using a workshop method that included stress management techniques, confidence building, and motivational strategies. The results were measured using pre-test and post-test questionnaires, and analysed with descriptive statistics and paired t-tests. The analysis showed a significant increase in participants' motivation and confidence, with an average increase of 15 points. A total of 75% of participants experienced a significant increase in motivation, 16.67% experienced a moderate increase, and 8.33% showed no significant change. The psychological training proved effective in enhancing the achievement motivation of MTQ participants in Tapin Regency. These results are expected to help participants achieve better performance in MTQ competitions.